Nilai Religius Dalam Novel Hafalan Shalat Delisa Karya Tere Liye Dan Implikasinya Terhadap Pembelajaran Apresiasi Sastra Di Sekolah Menengah Atas - Gunawan, Heri Indra (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This thesis aims to reveal the religious values contained in the novel Hafalan Shalat Delisa by Tere Liye and Implications literary appreciation learning related to aspects of genetic structuralism. The method used is qualitative descriptive data is described in terms of the actual reality in the form of writing, then analyzed and interpreted objectively then described according to the research objectives. The process of data collection include observation, documentation and interview. The research instrument is the researchers themselves who assisted with job analysis tables. It was concluded that the novel Hafalan Shalat Delisa by Tere Liye  contains many works of religious values such as faith, sharia and morality. It dkuatkan with the results of the analysis showed the value of faith by 21.88%, 28.13% and the value of sharia moral values sebsar 50%. Thus, in the novel Hafalan Shalat Delisa Tere Liye work is the most dominant moral values in the whole course of the story. Then to the intrinsic elements of a novel form of theme, plot, character and characterization, background, mandate, and style to form a unity intact and logical story, bursting with religious values. The implications of this study was associated with literary appreciation learning in high school (SMA) in particular novel Hafalan Shalat Delisa can be used as learning materials and applied in the learning process as outlined in the lesson plan. Besides religious values contained in the novel, helped establish character education learners.religious values